Molecular detection of Philaenus spumarius DNA in predators gut - Lantero, Ester (2020)
X. fastidiosa is one of the most destructive pathogens of olive orchards. Its recent arrival to Europe can cause important losses, with possible drastic consequences for the sector. Philaenus spumarius (Linnaeus 1758) was identified as vector of X. fastidiosa in Europe and finding candidate natural enemies of P. spumarius is essential to design environmentally friendly control strategies against X. fastidiosa. Generalist predators, such as spiders, arise as important potential biocontrol agents. In this context, a set of species-specific primers for detecting the presence of P. spumarius DNA in the gut of predatory arthropods is being developed. All primers will be tested for checking cross-reactive amplification of arthropods DNA and evaluated in heterospecific mixes of nucleic acids. Subsequent feeding trials will be conducted using Synemaglobosum (Fabricius 1775), an important spider species in olive groves from Mirandela, Portugal. These trials will allow determining the detection efficiency of the primers designed and also they will be the starting point to detect predation in field trials. These primers therefore provide a very useful tool for screening the gut contents of potential predators of P. spumarius, and can thus reveal candidate species for this species biological control.